Estimation of water volume in La Esperanza dam (Manabí, Ecuador), using bathymetry and geographic information systems (Revista Científica Ciencias Naturales y Ambientales, 2023)
This study consisted of determining the operating volume in La Esperanza reservoir through the bathymetric method of 3D positioning, using Garmin echoMAP™ echo sounder in conjunction with the application of geographic information systems (GIS). A digital elevation model “DEM” of resolution 12.5 m x 12.5 m, downloaded from the ALOS PALSAR satellite was coupled to obtain the area and digital topographic relief of the basin. In addition, two polynomial equations as a function of level, volume and area of the reservoir were estimated through a regression analysis by which a maximum operating volume of 428.64 Hm3 was obtained (elevation 66 m.a.s.l.), with a water mirror extension of 2,348.55 ha. In conclusion, the determination of the volume with technological devices and cartographic construction software is a key part of the diagnosis in water management and essential in the analysis for the correct management of reservoir volume in La Esperanza dam.